Pemanfaatan Algoritma Tiktok Dan Instagram Untuk Meningkatkan Brand Awareness - Susanto, Graciella; Leo, Deonvito; Evelyn, Rachel; Felicio, Hubert (Peneliti.net, 2023)
TikTok, a platform for sharing short videos, has rapidly gained popularity with over 1 billion monthly active users worldwide. Instagram, a platform for sharing photos and videos, also boasts more than 1 billion monthly active users. This journal aims to analyze and explore the utilization of TikTok and Instagram algorithms as effective strategies to enhance brand awareness. Employing a qualitative descriptive research approach, we conducted a study to understand the fundamental principles behind the TikTok and Instagram algorithms and identified various strategies that can be employed to achieve optimal outcomes in enhancing brand awareness through these platforms. Data collection was performed through literature review and analysis of relevant content. The gathered data were then subjected to descriptive analysis to comprehend how these algorithms influence content presentation to users and to outline effective methods for optimizing content and user interactions. The findings of this research provide comprehensive insights into leveraging TikTok and Instagram algorithms to bolster brand awareness.